Structure and Function of the Polypeptides in Simian Virus 40 I. Existence of Subviral Deoxynucleoprotein Complexes - Huang, Eng-Shang (1972)
Velocity sedimentation analysis of simian virus 40 degraded in alkaline buffers, pH 10.5, yields two components: soluble protein containing the largest polypeptides, VP1 and VP2, of the virion, and a deoxynucleoprotein complex (DNP-I) containing the viral deoxyribonucleic acid (DNA) and the small polypeptides, VP4, 5, and 6, and all or part of VP3. Dissociation of DNP-I by equilibrium centrifugation in CsCl yields a complex (DNP-II) of the viral DNA and residual, tightly bound polypeptide; VP4, 5, and 6, but not VP3, are recovered after separation from DNP-II. Treatment of the virus with β-mercaptoethanol and iodination experiments suggest that VP1 and VP2 might exist as compact structures cross-linked with disulfide bonds, perhaps forming the capsid. VP4, 5, and 6 form a relatively stable complex with the viral DNA and are supposed to be the internal proteins. The location of VP3 is not well defined; at least a portion of it is tightly bound to the viral DNA.